Self-esteem of youth participating in theatre performance: a Malaysian scenario - Yee, Wendy Mei Tien; Hamzah, Azimi; Uli, Jegak; Suandi, Turiman (Universiti Putra Malaysia Press, 2005)
A major developmental task during adolescent is the development of a sense of identity. The success of this stage of development will be the basis for development in the next stage of the developmental as a youth; where the development task is to build intimate relationship. Youth with a strong sense of self-esteem will establish better relationship and greater intimacy with another person. In this aspect, theatre is identified as one of the common developmental programs used because through performing, the youth are able to project a new identity and discover themselves. The study was aimed at identifying the extent of the self-esteem development among the youth as a result of participating in theatre performances and identifying the most influential theatre performance elements that contributed to the development of self-esteem. The findings of the study indicated that youth who participated in the theatre performances had a higher level of self-esteem.